Assembly and dispersal history of continental blocks within the Altun-Qilian-North Qaidam mountain belt, NW China. Issue 4 (4th March 2019) - Fu, Changlei; Yan, Zhen; Guo, Xianqing; Niu, Manlan; Cao, Bo; Wu, Qi; Li, Xiucai; Wang, Zongqi
ABSTRACT: The continental arc and intraplate magmatic rocks occur widely within the Altun-Qilian-North Qaidam (AQNQ) region of NW China and play a key role in reconstructing the assembly and dispersal history of micro-continental blocks within a complex orogenic system. In the South Qilian belt, amphibolites from the Hualong Complex can be subdivided into four types based on their lithologies, ages, and tectonic affinities. Type I is characterized by garnet and Proterozoic detrital zircons, indicating a metasedimentary origin. Type II and IV amphibolites are tholeiitic and calc-alkaline, respectively, and characterized by enrichment in LREES, Th, U, and Ba, accompanied by depletion in Nb and Ta, indicating a continental arc setting on an active continental margin. Type III is alkaline with ocean island basalt affinity and considered to have intraplate, rift-related origins. SHRIMP U-Pb dating and previous studies suggest that type II, III, and IV amphiboltes are formed at 1126 Ma, 882 Ma, and 470 Ma, respectively, which corresponds to 1126–895 Ma continental arc magmatism, 882–580 Ma rifted-related magmatism, and 522–440 Ma continental arc magmatism within the AQNQ. The three episodes of magmatism further demonstrate the processes of assembly and breakup of the Proterozoic supercontinent Rodinia and reassembly of the Altun-Qilian-North Qaidam orogenic belt.